A Study on the Role of Salman Rushdie to Preserve Indian History: Exploring the Fusion of History and Fiction in Salman Rushdie's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2013)
History in its varied forms is focused on and is the mainthrust area of the research work. The project begins by exploring the nexusbetween history and fiction through the ages, up to the post modem andpost-colonial times. This relationship between history and fiction forms thebasis of various histories that are represented in the novels of Rushdie. Therepresentation of politics in literature, political figures and events, areaesthetic representations of facts in fiction. Politics is not alwaysinterlaced with the narration; sometimes it is symbolic and often allegorical.Rushdie filters world history, national history, invasions and explorationsrecorded in historical accounts and the post-colonial interpretations ofcolonial power - in all his works. The fictional life of the narrator is fused,interspersed, intertwined and even sometimes entangled with his own ancestralhistory; autobiographical elements from the narrator are interwoven with theauthor's life. My study further explores the relationship between the privateand the public. Culture, myths, religion, tradition, heritage - blend andmerge, presenting a curiously hybrid picture. The final area that this studyfocuses on includes geographical locale, literary allusions and the creativeusage of language, highlighting their historical perspective as mentioned inthe novels of Rushdie. Thus, the research work is an attempt to bring forthvarious histories, work on their relevance and draw out theirinter-relatedness. The critical framework used is based on the theories ofmagic realism; inter texuality, historiographic metafiction, indeterminacy,deconstruction, hybridity, fragmentation, parody and so on.